Aplikasi Probe Untuk Penilaian Capaian Pembelajaran Mahasiswa Pada Kurikulum OBE (Outcame-Based Education) - Ishaq, Usep Mohamad; Wicaksono, Mochamad Fajar; Nurhayati, Sri (Computer Engineering Departement, Universitas Komputer Indonesia, 2023)
The purpose of this study was to create a web-based PROBE (OBE measurement) application that can provide information on the results of learning assessments using the OBE (outcome-based education) curriculum to students, and provide convenience to related parties in managing the OBE curriculum in the Computer Systems Study Program. OBE is a teaching approach that influences the learning process starting from curriculum design, learning outcomes, learning methods, and forms of evaluation of learning. Implementation of the OBE curriculum will not work without a system for measuring student learning outcomes. To carry out these measurements, it is necessary to design and build a student learning achievement assessment system through a software application in order to obtain ease of input, information processing, and access to the achievement of each learning outcome in CPL and CPMK. Therefore, the solution given to answer this problem is the need for an OBE application that can provide information on the results of student learning assessments. The contribution of this research is to provide convenience to related parties in viewing student learning achievements, so that it can be used for policies in terms of curriculum revision in Study Programs. The method used in this research is a case study approach where the case studies are taken from curriculum data for the 2020 Computer Systems Study Program. For making applications using the waterfall method, and analysis of functional system requirements using a structured approach. The results of this study indicate that 100% of the functionality of the application is running according to the functional requirements made, and the system has provided information on student achievement scores per academic year.